The Effects of Trade Facilitation on Indonesian Fisheries Export - Tiurmaida Krisanty Sitompul; Sahara Sahara; Lukytawati Anggraeni (Jurnal Manajemen & Agribisnis, 2018)
The growth in the volume and export value of fishery subsector shows the importance role of its sector to Indonesian economy. The export performance is influenced by many aspects, including trade facilitation. The problem faced by Indonesia is the low quality of trade facilitation resulting in relatively high trade costs, and this will affect the export performance. This research aims to analyze the effect of trade facilitation as well as other related variables on the Indonesia export in the fishery subsector, shrimp commodity exports, and export of tuna, mackerel tuna, as well as skipjack tuna. This study used panel data with ten years time series from 2007 to 2016, and the cross section data included ten major export destination countries. The data were analyzed using the gravity model with fixed effect estimation method. The study results showed that trade facilitation and other related variables had an effect on Indonesian fishery, shrimp, and tuna, mackerel tuna, as well as skipjack tuna exports. Based on the research results, Indonesian fishery exports can be improved by, firstly improving capacity and quality port infrastructure. Secondly, improving capacity and quality of electricity supply. Thirdly, the institutional quality is primarily concerned with ethics and corruption, and fourthly, the efficiency of trade across border needs to be improved in the hope of increasing the Indonesian export in the fishery subsector.Keywords: export, fishery, gravity model, trade facilitation